Beyond 'local' food: how supermarkets and consumer choice affect the economic viability of small‐scale family farms in Sydney, Australia. Issue 1 (15th November 2015) - James, Sarah W
Abstract : The localisation of food production, particularly in the form of urban/peri‐urban agriculture, is only gaining increasing public and political attention in industrialised nations such as Australia amid growing concerns about urban sustainability. Small‐scale family farmers on the peri‐urban fringe of cities such as Sydney, Australia's largest city, are considered key actors in the creation of a more sustainable and just urban food system by those advocating for food system change. The assumed alterity of such small‐scale farmers from the so‐called 'mainstream' food system, however, has led to a focus on localised threats such as urban development and solutions such as alternative food networks. This localised focus risks neglecting the way in which small‐scale family farmers, such as those on Sydney's urban fringe, are directly connected to and reliant on the mainstream for their economic viability. Emphasising the importance of issues such as supermarket power and consumer choice, this paper illustrates that it is necessary to examine the continuing connection between the mainstream system and 'local', small‐scale producers to achieve food system change.